Diagnostic and prognostic significance of alpha-defensin in patients with chronic heart failure during 2-year follow-up - Joanna Banach; Łukasz Wołowiec; Daniel Rogowicz; Wojciech Gilewski; Katarzyna Buszko; Danuta Karasek; Piotr Małyszka; Walery Zukow; Władysław Sinkiewicz (Journal of Education, Health and Sport, 2018)
Background